Pembuatan, Karakterisasi dan Uji In Vitro Nanopartikel Emas Berbasis Konjugat Gom Arab-Vinkristin - Ratih Dyah Pertiwi; Joshita Djajadisastra; ABDUL MUTALIB; Anung Pujiyanto (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Gold nanoparticles (AuNP) are potentially developed as nanomedicine because AuNP is easily synthesized, functionalized, and biocompatible. With gum arabic as a stabilizer, vincristine was conjugated with gold nanoparticles. As a reducing agent, it used 0.02 M Natrium Boro Hidrat (NaBH4) solution. Gold nanoparticles (AuNP) coated with conjugated gum Arabic (GA) and vincristine (VCR) were successfully synthesized and characterized. The conjugation of GA-VCR and AuNP displayed a narrow hydrodynamic particle size distribution with average size < 100 nm by TEM and PSA (particle size analyzer). We investigated the cytotoxic activity of conjugated vincristine-gum arabic-gold nanoparticle by tetrazolium salt assay (MTT) using cancer cell line CCR-CEM. Cytotoxic activity of conjugated VCR-GA-AuNP before and after purification by Size Exclusion Chromatography (SEC), against leukemia cell line CCRF-CEM, was described by IC50 value. All formulation had a cytotoxic of activity with IC50 <20 μg/ml. The IC50 of samples against CCRF cell line were 1,026 μg/mL and 2,607 ug/mL, respectively.